A Novel Structurally Stable Multiepitope Protein for Detection of HCV. (28th January 2016) - Galdino, Alexsandro S.; Santos, José C.; Souza, Marilen Q.; Nóbrega, Yanna K. M.; Xavier, Mary-Ann E.; Felipe, Maria S. S.; Freitas, Sonia M.; Torres, Fernando A. G.
Abstract : Hepatitis C virus (HCV) has emerged as the major pathogen of liver diseases in recent years leading to worldwide blood-transmitted chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. Accurate diagnosis for differentiation of hepatitis C from other viruses is thus of pivotal importance for proper treatment. In this work we developed a recombinant multiepitope protein (rMEHCV) for hepatitis C diagnostic purposes based on conserved and immunodominant epitopes from core, NS3, NS4A, NS4B, and NS5 regions of the virus polyprotein of genotypes 1a, 1b, and 3a, the most prevalent genotypes in South America (especially in Brazil). A synthetic gene was designed to encode eight epitopes in tandem separated by a flexible linker and bearing a his-tag at the C-terminal end. The recombinant protein was produced in Escherichia coli and purified in a single affinity chromatographic step with >95% purity. Purified rMEHCV was used to perform an ELISA which showed that the recombinant protein was recognized by IgG and IgM from human serum samples. The structural data obtained by circular dichroism (CD) spectroscopy showed that rMEHCV is a highly thermal stable protein at neutral and alkaline conditions. Together, these results show that rMEHCV should be considered an alternative antigen for hepatitis C diagnosis.